Zderzenie kulturowe. Społeczeństwo pomorskie wobec wojska polskiego w 1920 roku (Kronika Bydgoska, 2018)
The Polish Army, which was taking over Pomerania in winter 1920 based on the provisions of the Treaty of Versailles, was enthusiastically welcomed by the local community. However, the behavior of Polish officers and soldiers, most of whom were coming from the regions of Poland that were annexed by different countries, was bothering the residents of the land that used to be under the Prussian rule, since they had been accustomed to exemplary order and deep respect for the rules of co-existence, moral principles and legal regulations. In this context, there had been many conflicts and complaints of local folks who criticized the behavior of military personnel. They expressed these objections, with ranging gravity, in their letters addressed to regional and military authorities - sent by local officials, county commissioners and private individuals. They were so alarming that a special parliamentary committee was sent to Pomerania to examine this new situation. However, the results of its works were unnoticed, since they coincided with the Polish-Soviet War. It took several years for the situation in Pomerania to be restored to normal and the reluctance of the local community to the Polish army to be eased.